Crude Constraints: Oil Price Asymmetries and the Growth Path of Saudi Arabia’s Services Sector - Sharaf, Mesbah Fathy; Shahen , Abdelhalem Mahmoud (International Journal of Energy Economics and Policy, 2025)
This study explores the dynamic relationship between oil dependency and the growth of the services sector in Saudi Arabia over the period 1980–2023. Using both linear Autoregressive Distributed Lag (ARDL) and nonlinear ARDL (NARDL) models, we examine whether oil price shocks exert symmetric or asymmetric effects on the share of services in GDP. The results reveal that oil rents significantly reduce the services sector’s contribution in the long run, highlighting structural dependencies within the economy. Short-run dynamics vary across macroeconomic indicators, with real oil prices showing more immediate but less persistent effects. The NARDL model provides new insights, uncovering strong asymmetries: negative oil price shocks have a greater and more significant adverse impact on services value added than positive shocks, both in the short and long term. Unit root tests support the ARDL framework, and bounds testing confirms cointegration. These findings underscore the challenges of reducing oil dependence and suggest that economic diversification strategies under Saudi Vision 2030 must account for the asymmetric vulnerabilities introduced by oil price volatility.